2017
DOI: 10.1177/0340035217744235
|View full text |Cite
|
Sign up to set email alerts
|

Usage of academic social networking sites by Karachi social science faculty

Abstract: The last decade has seen the emergence of academic social networking sites as a vehicle for scholars to promote their research and communicate with other scholars in their field. Given the small number of studies on the use of such sites by Pakistani academics, the authors conducted an exploratory study of social science faculty members at five Karachi (Pakistan) public sector universities. Analysis of the 68 valid responses revealed that the primary reason for accessing an academic social networking site was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…Some studies dealing with cross-cutting topics are assigned to multiple themes. (Agarwal et al, 2016;Ali, Wolski, & Richardson, 2017;Allahar, 2017;Asmi, 2018;Asmi & Margam, 2018;Baro, Tralagba, & Ebiagbe, 2018;Bhardwaj, 2017;Calvi & Cassella, 2013;Camilleri, 2017;Conole & Alevizou, 2010;D'Alessandro et al, 2020;Deng, Tong, & Fu, 2018;González-Solar, 2018;Goodwin et al, 2014;Gorska et al, 2020;Greifeneder et al, 2018;Gruzd, Staves, & Wilk, 2012;Hoffmann et al, 2016;Jeng et al, 2017;Jordan, 2019b;Kapidzic, 2020;Koranteng & Wiafe, 2019;Laakso, Lindman, Shen, Nyman, & Björk, 2017;Manca, 2018;Martín, Orduna, & Delgado, 2018;Meishar-Tal & Pieterse, 2017;Ortega, 2017;Ortega, 2016;Ostermaier-Grabow & Linek, 2019;Li et al, 2018;Ponte & Simon, 2011;Radford, Kitzie, Mikitish, Floegel, Radford, & Connaway, 2018;Salahshour et al, 2016;Salahshour, Nilashi, Mohamed Dahlan, & Ibrahim, 2019;Singson & Amees, 2017;Vasquez et al, 2015;Williams & Woodacre, 2016;Yim & Shin, 2013;Ali & Richardson, 2018;…”
Section: Descriptive Abstract and Content Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies dealing with cross-cutting topics are assigned to multiple themes. (Agarwal et al, 2016;Ali, Wolski, & Richardson, 2017;Allahar, 2017;Asmi, 2018;Asmi & Margam, 2018;Baro, Tralagba, & Ebiagbe, 2018;Bhardwaj, 2017;Calvi & Cassella, 2013;Camilleri, 2017;Conole & Alevizou, 2010;D'Alessandro et al, 2020;Deng, Tong, & Fu, 2018;González-Solar, 2018;Goodwin et al, 2014;Gorska et al, 2020;Greifeneder et al, 2018;Gruzd, Staves, & Wilk, 2012;Hoffmann et al, 2016;Jeng et al, 2017;Jordan, 2019b;Kapidzic, 2020;Koranteng & Wiafe, 2019;Laakso, Lindman, Shen, Nyman, & Björk, 2017;Manca, 2018;Martín, Orduna, & Delgado, 2018;Meishar-Tal & Pieterse, 2017;Ortega, 2017;Ortega, 2016;Ostermaier-Grabow & Linek, 2019;Li et al, 2018;Ponte & Simon, 2011;Radford, Kitzie, Mikitish, Floegel, Radford, & Connaway, 2018;Salahshour et al, 2016;Salahshour, Nilashi, Mohamed Dahlan, & Ibrahim, 2019;Singson & Amees, 2017;Vasquez et al, 2015;Williams & Woodacre, 2016;Yim & Shin, 2013;Ali & Richardson, 2018;…”
Section: Descriptive Abstract and Content Analysismentioning
confidence: 99%
“…Quantitative approaches using surveys are the primary research methodology used in these papers. The following factors stimulated users to join and use ASNs: (1) connecting with colleagues, (Calvi & Cassella, 2013;Gruzd et al, 2012;Salahshour et al, 2016;Yousuf et al, 2018) ; (2) sharing/disseminating published and unpublished research works, (Baro et al, 2018;Conole & Alevizou, 2013;Gruzd et al, 2012) ; (3) acquiring materials, (Calvi & Cassella, 2013;Gruzd et al, 2012;Salahshour et al, 2016;Ali & Richardson, 2018);…”
Section: Motivation and Uses Of Asns (Theme I)mentioning
confidence: 99%
See 2 more Smart Citations
“…Aleryani, Mofleh and Alariki (2017) found that more than 33% of researchers are not aware of academic social network sites. Ali and Richardson (2017) showed that accruing citations was the main reason for the respondents to upload their publications. The studies by Bardakcı, Arslan and U¨never (2017), Meishar-Tal and Pieterse (2017), and Mering (2017) proved that the use of social network sites enhanced the research collaboration and information development with researchers across the globe.…”
Section: Literature Reviewmentioning
confidence: 99%